2009
DOI: 10.1074/jbc.m109.035345
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of ΔF508-CFTR by the SGK1/Nedd4-2 Signaling Pathway

Abstract: The most common mutation in cystic fibrosis (CF) is ⌬F508, which is associated with failure of the mutant cystic fibrosis transmembrane conductance regulator (CFTR) to traffic to the plasma membrane. By a still unknown mechanism, the loss of correctly trafficked ⌬F508-CFTR results in an excess of the epithelial sodium channel (ENaC) on the apical plasma membrane. ENaC trafficking is known to be regulated by a signaling pathway involving the glucocorticoid receptor, the serum-and glucocorticoid-regulated kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 49 publications
4
84
1
Order By: Relevance
“…The observed cooperativity in maturation and functional rescue between SYVN1 knockdown and low temperature suggests a shared group of genes or protein complexes involved in ⌬F508-CFTR ubiquitination and degradation. If such overlap exists it might provide insight into how, in the presence of low temperature or SYVN1 knockdown, ⌬F508-CFTR escapes the Hsc70-CHIP E3 complex that monitors the conformation of different regions of nascent CFTR (36,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed cooperativity in maturation and functional rescue between SYVN1 knockdown and low temperature suggests a shared group of genes or protein complexes involved in ⌬F508-CFTR ubiquitination and degradation. If such overlap exists it might provide insight into how, in the presence of low temperature or SYVN1 knockdown, ⌬F508-CFTR escapes the Hsc70-CHIP E3 complex that monitors the conformation of different regions of nascent CFTR (36,38).…”
Section: Discussionmentioning
confidence: 99%
“…Distinct E3 ubiquitin ligases have been identified that are involved in ⌬F508-CFTR ubiquitination (34,35). DNAJB12, HSPA8 (Hsc70), and RNF5 (RMA1) are involved in co-translational ubiquitination of ⌬F508-CFTR (36, 37), whereas CHIP (STUB1) is involved with ubiquitination of full-length ⌬F508-CFTR (36,38). RNF5 (E3 ubiquitin-protein ligase) and AMFR (Gp78; E3 ubiquitin-protein ligase) are integral to the ⌬F508-CFTR ubiquitination machinery in the ER (34,37).…”
Section: Rna Interference Screen Of 13 Candidates Reveals Role For Symentioning
confidence: 99%
“…[23][24][25][26][27][28][29] The two genes interacting with EnaC are Nedd4L (neural precursor cell expressed, developmentally downregulated 4-like) and PRSS8 (prostasin). [30][31][32] The last group consists of three genes that are involved in CFTR trafficking, AHSAI (activator of heat shock 90-kDa protein ATPase homolog 1), CALR (calreticulin) and KRT19 (cytokeratin 19). [33][34][35][36] Most candidate gene and whole-genome association studies so far focused on time point measurements of only one or two lung function parameters.…”
Section: Introductionmentioning
confidence: 99%
“…CFTR that is rescued to the cell surface by lower temperature or small molecules is quickly retrieved from the cell surface and trafficked to the lysosome for degradation (11,12). Prolongation of recycling and cell surface residence time is desirable to enable potentiation of chloride channel openings by molecules such as ivacaftor (25).…”
Section: Figmentioning
confidence: 99%
“…We showed that imposing monoubiquitination on wild-type (wt) and F508del CFTR leads to increased preservation of band B core glycosylated CFTR (7). Ubiquitination of CFTR is important for its regulation and quality control process (8)(9)(10), including ubiquitin-mediated proteasomal degradation (8,9) and recycling (11,12). However, the ubiquitination sites on wt CFTR, mechanism of degradation, and regulation of recycling are largely unknown.…”
mentioning
confidence: 99%